Evapotranspiration of a maize stand as related to soil moisture (case study) - MATEJKA, František; ROŽNOVSKÝ, Jaroslav; CHALUPNÍKOVÁ, Blanka; HURTALOVÁ, Taťjana (Contributions to Geophysics and Geodesy, 2021)
The cumulative evapotranspiration of a maize stand growing at Žabčice situated in the south-east part of the Czech Republic was determined over the periods from planting to harvest in three consecutive years 1999, 2000 and 2001. In 1999, when the maize stand was sufficiently supplied with soil water, the sum of the evapotranspiration reached 279.7 mm during the period of sixteen weeks after planting. In the next year, the water regime of the maize stand was strongly influenced by significant decrease of the soil water content in the root zone, and consequently, the cumulative evapotranspiration during the same period was only 63.8% of the cumulative evapotranspiration over the comparable time interval in the season 1999. Similar reductions in the soil water content and evapotranspiration were recorded during the vegetation period 2001, as well. The mean daily sums of the evapotranspiration averaged over the periods of sixteen weeks after planting were 2.48 mm/day in 1999, but only 2.06 mm/day in 2000 and 1.73 mm/day in 2001. It followed from further analysis that the soil water availability practically did not affect the evapotranspiration, when at least 58.2% of extractable soil water was present in the root zone, but below this value, the evapotranspiration decreased linearly with the decrease in the soil water content. When the amount of available water for plants approaches the wilting point, the actual evapotranspiration is negligible.